2019
DOI: 10.1186/s13071-019-3800-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of three intestinal protozoans in hospitalized children with different disease backgrounds in Zhengzhou, central China

Abstract: BackgroundCryptosporidium spp. and Giardia duodenalis are major intestinal pathogens that can cause diarrheal diseases in humans, especially children. Enterocytozoon bieneusi is another parasite which can cause gastrointestinal tract disorders, with diarrhea being the main clinical symptom. However, few genetic studies of these parasites in pediatric inpatients in China have been published.MethodsTo assess the genetic characteristics and epidemiological status of these parasites, a total of 2284 fecal samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Among the >17 human-pathogenic species of microsporidia, Enterocytozoon bieneusi is the most common [ 2 , 3 ]. It causes diarrhea and other gastrointestinal symptoms in both immunocompetent and immunocompromised persons [ [4] , [5] , [6] , [7] , [8] ]. Among them, AIDS patients and children are especially susceptible to E. bieneusi [ 4 , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the >17 human-pathogenic species of microsporidia, Enterocytozoon bieneusi is the most common [ 2 , 3 ]. It causes diarrhea and other gastrointestinal symptoms in both immunocompetent and immunocompromised persons [ [4] , [5] , [6] , [7] , [8] ]. Among them, AIDS patients and children are especially susceptible to E. bieneusi [ 4 , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…Another report described the occurrence of the Group 2 genotype BEB6 (reported as SH5) in hospitalized children in Shanghai [ 17 ]. Both J and BEB6 were identified in children attending three hospitals in Zhengzhou [ 6 ]. In addition, several reports showed the occurrence of Group 2 genotypes I, J, BEB4, BEB6, BEB8, BSH, CD6, CM4, CM5, CM7, CM9, CM20, and CM21 in wild or captive nonhuman primates in China [ [24] , [25] , [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these assemblages, assemblages A and B are considered to be zoonotic, while other assemblages are mostly host specific [1]. In addition, assemblage E is the dominant genotype of G. lamblia occurring in cattle [5][6][7][8], and zoonotic assemblages A and B have also been identified in cattle and humans in some studies [9][10][11][12][13]. However, there are some studies that have found assemblage E existing in human cases [5,14,15].…”
mentioning
confidence: 99%
“…In China, genotype D was the most prevalent genotype discovered in 17 samples from symptomatic children, HIV-positive patients, and HIVnegative individuals. Furthermore, genotype D was observed in not less than 15 animal species, river water and wastewater [40] . Our results agree with other studies that reported the zoonotic potential of genotype D [32,40,41] , and that it is a non host specific genotype with a broad host and geographic range [42,43] .…”
Section: Discussionmentioning
confidence: 95%